STRATEGI PENGEMBANGAN IKAN NILA(Oreochoromis niloticus) - Gustina Siregar; Hendra Sunarno; Samsidar . (AGRIUM: Jurnal Ilmu Pertanian, 2014)
Increased production of tilapia farming as the main priority can be done through the application of SWOT Analysis Method. The method involves review of business location and optimization of workforce to improve production. Method used in this research is case method. The research was conducted at Desa Ujung, Singkil, Aceh Singkil District, Aceh Province. The samples were taken using purposive sampling method. Data collection in this research consists of primary data taken from interview and analyzed using SWOT analysis method and secondary data obtained from Singkil SDO, Aceh Singkil district. The results of the research through descriptive SWOT analysis show that matrix value of internal factor at 0,33 while matrix value of external factor at 0,379, the use of  ST (Strengths and Threats) analysis indicates the company to be able to overcome the threats using the strengths from internal factor. Strategy used to gain long term opportunities can be done through utilization of internal strengths using diversification method. Keywords :Tilapia, SWOT Analysis, Internal Factor, External Factor.